Graphene-Skinned Fiber with Fine-Tunable Electrical Resistance via Radical and Substrate Engineering for Electromagnetic-Thermal Fabric - Liang, Jie; Li, Zhaochen; Ye, Fang; Cao, Yuchen; An, Yi; Fan, Xiaomeng; Song, Qiang (Nano-Micro Letters, 2026)
This work demonstrates a radical-manipulation strategy for synthesizing graphene (Gr)-skinned SiO2 fabric via low-pressure chemical vapor deposition using methanol precursor. Controlled pyrolysis at high temperature regulated C1/C2/C6 radical ratios, enabling microstructure engineering. Substrate effects governed bilayer evolution. SiO2 imposed lower adsorption energy of C1 and higher diffusion barriers of radical compared to Gr, promoting edge defects in subsurface G1-type Gr layers, whereas reduced substrate constraints facilitated low-defect G2-type Gr growth on top of G1-type Gr. Synergistic control of gas-phase kinetics and substrate dynamics enabled fine-tunable sheet resistance (26–150 Ω sq−1), establishing Gr-skinned fibers as multifunctional platforms for integrated electromagnetic-thermal management systems. When addressing the needs of electromagnetic communication and electrothermal deicing, laser-etched band-pass frequency selective surface structures of Gr-skinned fabric were fabricated to achieve electromagnetic wave (EMW) transmittance while maintaining Joule heating capability. A sandwich structure was prepared by laminating the Gr-skinned fabric with EMW transparent sheets exhibiting voltage-dependent transmittance, simultaneously sustaining broadband transmission and effective heating. This work demonstrates a strategy to mitigate the longstanding conductivity-EMW transparency trade-off in Gr-functionalized fibers through a multiscale engineering that coordinates microscopic structural regulation with macroscopic patterning, thereby unlocking next-generation smart composites for 5G/6G wearables, aerospace radomes, and beyond. Highlights: 1 The composition of C1/C2/C6 radicals is strategically regulated by temperature, dictating the growth of either defective or highly textured graphene microstructures. 2 A synergistic strategy involving radical manipulation and substrate effect via methanol- chemical vapor deposition enables precise control of graphene microstructure, allowing fine tuning of sheet resistance from 26 to 150 Ω sq−1. 3 Laser-patterned band-pass frequency selective surface and a sandwich structure synergistically achieve excellent broadband wave transmission (7.29 GHz) and effective Joule heating (72 °C).